Análise estrutural e topológica de peptídeos bioativos em meios biomiméticos de membranas - Victor Hugo de Oliveira Munhoz (2012)
This work consists of studies on the structure and interactions with membrane-mimetic media of the antimicrobial peptides distinctin, an heterodimer composed of two peptide chains (chain 1 and chain 2) covalently bonded through a dissulfide bond and isolated from the skin ofPhyllomedusa distincta anurans, native from the Brazilian Atlantic Forest; Hylaseptin P2 (HSP2) and the phenylseptins [L-Phe2]-Phenylseptin (L-Phes) and [D-Phe2]-Phenylseptin (D-Phes), all three isolated from Hypsiboas punctatus anurans, found on the Amazon tropical forest. All these peptides show considerable activity against both Gram-positive and Gram-negative bacteria, reason why there is growing interest in better understanding the mechanistic pathway these molecules follow on exerting their biological activities. The most widely accepted model for such mechanism is the Shai-Matsuzaki-Huang model (Matsuzaki, 1999; Shai, 1999; Huang, 2000; Yang, 2000; Papo, 2005), which takes into account a strong influence of the peptides structures on theirbiological activities. Hence the need to study these peptides on a structural level in order to propose a consistent model. The aforementioned peptides had their structures studied and determined by means of Circular Dichroism (CD) and solution Nuclear Magnetic Resonance (NMR). The results showed that all peptides presented well-ordered tertiary structures, all of them also quite rich on a-helicalsecondary structure and with a sharp amphipathic character. Distinctins structural model, albeit showing considerable ordering when taking into account each monomeric chain separately, did not present a very well-defined overall orientation of one chain in relation to the other. The CD results, however, indicated stark a-helical structuration for both the chains as well as for the heterodimer, although it suggests that the interaction between the peptide and the phospholipid is better described as an equilibrium with more than two states. For the HSP2, the results of the CD experiments on small unilamelar vesicles and the NMR experiments in 2,2,2-triluoroethanol (TFE) showed a high content of a-helix and the models derived from the NMR data also showeda sheer amphipathic character. For the phenylseptins, the NMR experiments in DPC also led to a-helix-rich structures, being that D-Phes showed a slightly higher structuration degree than LPhes. The solid-state NMR experiments were performed for HSP2 and the two phenylseptins,with mechanically-oriented samples containing 1-palmitoyl-2-oleoylphosphatidylcholine (POPC) bilayers and the peptides selectively-labeled with 15N and 2H. From the measurements of anisotropic properties such as 15N chemical shifts, and 2H quadrupolar splitting, it was possible to calculate the possible orientations for the structure determined from the solution NMR data. ForHSP2, the concomitant analysis of both solid-state and solution NMR results showed that the peptide interacts strongly with the bilayer, in way such that its hydrophobic side is in direct contact with the phospholipids aliphatic chains and in a quasi-paralell orientation in relation tothe bilayers surface. The epimers L-Phes and D-Phes, albeit showing very similar tertiary structures, their calculated orientations are significantly different, which suggests that these peptides interact with the bilayer in distinct manners when comparing one to the other.Another part of this work comprises the study of the HSP2 peptide-lyposome interactions thermodynamics through Isotermal Titration Calorimetry (ITC). These studies showed that the interaction in question is strongly dependent on the concentration of the peptideon the media and that, in spite of having a sharp electrostatic character at an initial moment which consist on the approximation of the peptide to the membrane, it is mostly maintained by hydrophobic interactions between the non-polar sidechains and the membranes hydrophobiccore. The analysis of these results together with the NMR ones, allowed us to build a more complete and detailed model for the interaction between the peptide and the bacterial membrane.